The Many Faces of Manhood: Examining Masculine Norms and Health Behaviors of Young Fathers Across Race. (September 2013) - Gordon, Derrick M.; Hawes, Samuel W.; Reid, Allecia E.; Callands, Tamora A.; Magriples, Urania; Divney, Anna; Niccolai, Linda M.; Kershaw, Trace
This study examined the relationship between the traditional masculine norms ("status, " "toughness" and "antifemininity") of 296 ethnically and racially diverse, young men transitioning to fatherhood and substance use (smoking, alcohol, marijuana, hard drugs) and health behaviors (diet, exercise). Participants were recruited from urban obstetric clinics in the Northeast United States. Logistic and multiple regression equations were constructed to examine the relationship between masculine norms and health behaviors. Moderator effects were also examined. Masculine norm "status" was most endorsed and "antifemininity" was least endorsed. African American young men had higher masculine norm scores than Latino and Whites. Different masculine norms were associated with health-promoting and health-undermining behaviors. Different racial groups who had higher scores on some masculine norms were more likely to engage in either health-promoting or health-undermining behaviors when compared with other ethnic groups in this study. These results observed different relationships between the traditional masculine norms measured and the substance use and health behaviors of diverse, young men transitioning to fatherhood. This may have implications for intervention strategies and future research.